Geological features of fluid zona-tion in multilayer field of Dnieper-Donetsk depression - Абєлєнцев, В. М.; Лур’є, А. Й.; МіщенкоЛ. O. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
Geological conditions of hydrocarbons occurrence in multilayer fields are reviewed to identify prospective underexplored areas on the example of North near-edge zone of Dnieper-Donetsk depression. The main factors of the geological structure multilayer fields as structural-tectonic, stratigraphic, lithofacies, morphological, filtration-capacitive, hydrogeological, thermobaric have been defined. Geological localization features of hydrocarbon deposits of multilayer fields in North near-edge zone of Dnieper-Donetsk depression were analyzed. According to the results of using the parameters of oil-and-gaz-saturation pore the volumes of hydrocarbon deposits were identified as well as features of hydrocarbon fields’ vertical zonation. This option more fully describes the internal, discrete structure of each of the fields. As a result of the comparison of effective oil-and-gaz-saturated pore volumes as to the section of each deposit of North near-edge zone of Dnieper-Donetsk depression a baseline horizon has been defined. The baseline horizon is characterized by most effective oil-and-gaz-saturation of pores volume. The features of fluid zoning for each field were identified relative to their base horizons. As the result three types of vertical zoning fluid deposits were identified. First - horizons with less oil-and-gaz-saturation pore volumes of the section lie below and above of the base horizon, second – lie below the base of the horizon; third - above the base horizon. According to the established zoning fluid typing the forecast of new horizons and underexplored areas within opened fields of Dnieper-Donetsk depression were made. In the second type of multilayer fields perspective horizons and underexplored areas were forecasted below the baseline horizons. In the third type of multilayer fields are forecasted above baseline horizons.